2016
DOI: 10.18235/0000262
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Larger Per Capita Incomes: How To Prioritize across Productivity Determinants?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…2 Evidence of the insufficiency of infrastructure investment in many emerging economies, including some in LAC, has come from an approach that measures investment gaps (see for example Fay et al, 2017;Dieppe, 2020;and Borensztein et al, 2014). However, the estimated gaps may not be reliable enough to guide priorities in a growth strategy based on what types of investment contribute most to raising per capita income (Izquierdo et al, 2016), or in a broader sustainable strategy (Rozenberg and Fay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 Evidence of the insufficiency of infrastructure investment in many emerging economies, including some in LAC, has come from an approach that measures investment gaps (see for example Fay et al, 2017;Dieppe, 2020;and Borensztein et al, 2014). However, the estimated gaps may not be reliable enough to guide priorities in a growth strategy based on what types of investment contribute most to raising per capita income (Izquierdo et al, 2016), or in a broader sustainable strategy (Rozenberg and Fay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other empirical evidence support this line of thinking: Quah (1997) analyzed the evolution of cross-section distributions to identify data patterns in the presence of heterogeneity; Liu and Stengos (1999) showed that initial output and schooling levels have nonlinear effects on growth rates and suggested the presence of multiple regimes; Alfò et al (2008) found that the explanatory power of the Solow growth model was enhanced when cross-country heterogeneity was considered; Galor (2007) segmented economies into three fundamental regimesslow growing economies, fast growing countries in a sustained growth regime, and economies in the transition between these regimes; Høyland et al (2012) also suggested to allocate countries into groups based on a criterion of similarity and to use the trade-off between within-group homogeneity and between-group heterogeneity; and Izquiero et al (2016) showed that the prioritization of the productivity determinants seems to be specific to the income per capita group to which a country belongs.…”
Section: Some Comments On Growth Regressionsmentioning
confidence: 99%
“…Despite the differences in methodology, we obtain similar results. Focusing on the two last jumps, Izquierdo et al (2016) highlight financial development and governance, infrastructure, integration and trade, labour and health-care services as key.…”
Section: Motivationmentioning
confidence: 99%